An inducible form of Nrf2 confers enhanced protection against acute oxidative stresses in RPE cells. (November 2017) - Vu, Khiem T.; Hulleman, John D.
Abstract: Increasing evidence suggests that overt oxidative stress within the retina plays an important role in the progression of age-related retinal decline, and in particular, in the disease age-related macular degeneration (AMD). Nuclear factor erythroid 2-like 2 (Nrf2) is a master transcription factor that upregulates numerous of antioxidant/detoxification genes. Nrf2 −/− mice develop progressive retinal degeneration that includes the formation of drusen-like deposits, lipofuscin, and sub-retinal pigment epithelium (RPE) deposition of inflammatory proteins. Furthermore, strategies that promote Nrf2 activation have shown promise for the treatment of cone/rod dystrophies and other forms of retinal degeneration. Herein we explored whether utilizing a small molecule-inducible version of Nrf2 confers additional protection against oxidative stresses when compared to a constitutively expressed version of Nrf2. Stable populations of human ARPE-19 cells were generated that express either constitutive FLAG-tagged (FT) Nrf2 (FT cNrf2) or doxycycline (dox)-inducible FT Nrf2 (FT iNrf2) at low levels (∼4.5 fold vs. endogenous). Expression of either FT cNRF2 or FT iNrf2 upregulated canonical antioxidant genes (e.g., NQO1, GCLC). Both FT cNrf2 and FT iNrf2 ARPE-19 cells were protected from cigarette smoke extract-induced nitric oxide generation to similar extents. However, only FT iNrf2 cells demonstrated enhanced resistance to doxorubicin and cumene hydroperoxide-mediated increases in mitochondrial superoxide and lipid peroxidation, respectively, and did so in a dox-dependent manner. These results suggest that therapeutic approaches which conditionally control Nrf2 activity may provide additional protection against acute oxidative stresses when compared to constitutively expressed Nrf2 strategies.